Fitness consequences of hybridization in a predominantly selfing species: insights into the role of dominance and epistatic incompatibilities - Clo, Josselin; Ronfort, Joëlle; Gay, Laurène (Heredity, 2021)
Studying the consequences of hybridization on plant performance is insightful to understand the adaptive potential of populations, notably at local scales. Due to reduced effective recombination, predominantly selfing species are organized in highly homozygous multi-locus-genotypes (or lines) that accumulate genetic differentiation both among- and within-populations. This high level of homozygosity facilitates the dissection of the genetic basis of hybrid performance in highly selfing species, which gives insights into the mechanisms of reproductive isolation between lines. Here, we explored the fitness consequences of hybridization events between natural inbred lines of the predominantly selfing species Medicago truncatula, at both within- and among-populations scales. We found that hybridization has opposite effects pending on studied fitness proxies, with dry mass showing heterosis, and seed production showing outbreeding depression. Although we found significant patterns of heterosis and outbreeding depression, they did not differ significantly for within- compared to among-population crosses. Family-based analyses allowed us to determine that hybrid differentiation was mostly due to dominance and epistasis. Dominance and/or dominant epistatic interactions increased dry mass, while decreasing seed production, and recessive epistatic interactions mostly had a positive effect on both fitness proxies. Our results illustrate how genetic incompatibilities can accumulate at a very local scale among multi-locus-genotypes, and how non-additive genetic effects contribute to heterosis and outbreeding depression.
Keywords: Epistasis, Genetic; Hybridization, Genetic; genetická epistáze; křížení genetické; Crosses, Genetic; Genetic Drift; genotyp; hybridizace genetická; Hybrid Vigor; genetický drift; hybridní efekt; Genotype